The Corporate Crime as The Power of Crime in The Economic Justification - Budianto, Agus (SASI, 2022)
Introduction: A corporation with strong capital support from its company, with its core business seeking as much profit as possible, is very vulnerable to carrying out activities that violate the law even though economically or financially these activities are correct.Purposes of the Research: The purpose is to find a wedge, where the location of economic activities that violate the law is interpreted as violating the law, because economic or financial crimes are closely related to legal reasoning.Methods of the Research: The type of research is normative juridical with analysis using legal documents in the form of primary legal materials, secondary legal materials, and tertiary legal materials.Results of the Research: The analysis show that the business expansion activities carried out by PT Jiwasraya are business activities that are justified by the economy or finance. However, because one of these activities involves state finances, it fulfills one of the elements of a criminal act of corruption. Activities that are justified in business are still getting attention by law because the nature of the crime is corporate crime, namely corporate crime which is carried out solely for the benefit of the corporation. Corporate crime will have the power to suppress society, so that the culture of the community will in some ways change and will indirectly threaten the concept of the rule of law in Indonesia.